Assessment of Urban Sustainability and Ecological Footprint towards Health Expenditure - Adibah Hussin; Nor Aziah Abd Kadir; Fazreena Mansor; Nur Fakhzan Marwan; Rosmah Nizam (Current Topics on Business, Economics and Finance Vol. 4, 2023)
Urban sustainability is one of the most crucial goals for a nation to pursue since it helps communities and society live in harmony and within legal boundaries. Better output and economic growth will be produced by the pleasant environment. The majority of researchers discovered that urbanisation will accelerate environmental damage. It contributes to environmental devastation and is one of the ecological imprints left by humanity. The nation’s level of health will be impacted by the growing ecological imprint. Air pollution can cause skin irritation, water pollution can induce diarrhoea, and so on. Since urbanisation refers to the demographic shift from rural to urban, it may have a direct impact on health expenditures. The cost of health care is rising along with the urban population. In order to increase the significance of urbanisation policy and reduce the ecological footprint and expenditures, it is imperative to have a deeper understanding of the precise mechanisms underlying their relationship. This allows the government to focus on other forms of expenditures for the development of the country.